2024
DOI: 10.3390/toxins16010031
|View full text |Cite
|
Sign up to set email alerts
|

What Is Fusarium Head Blight (FHB) Resistance and What Are Its Food Safety Risks in Wheat? Problems and Solutions—A Review

Akos Mesterhazy

Abstract: The term “Fusarium Head Blight” (FHB) resistance supposedly covers common resistances to different Fusarium spp. without any generally accepted evidence. For food safety, all should be considered with their toxins, except for deoxynivalenol (DON). Disease index (DI), scabby kernels (FDK), and DON steadily result from FHB, and even the genetic regulation of Fusarium spp. may differ; therefore, multitoxin contamination is common. The resistance types of FHB form a rather complex syndrome that has been the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…It is well noted that when humidity is favorable (Ma et al 2019), infection can occur any time after starting of anthesis in bread wheat (Mesterhazy 2020(Mesterhazy , 2024), but owering is the growth stage most susceptible to Fusarium infection (Miedaner et al 2021). In the present investigation, we used an arti cial infection-environment experiments designed to better understand the role of variable postanthesis moisture patterns on FHB development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well noted that when humidity is favorable (Ma et al 2019), infection can occur any time after starting of anthesis in bread wheat (Mesterhazy 2020(Mesterhazy , 2024), but owering is the growth stage most susceptible to Fusarium infection (Miedaner et al 2021). In the present investigation, we used an arti cial infection-environment experiments designed to better understand the role of variable postanthesis moisture patterns on FHB development.…”
Section: Discussionmentioning
confidence: 99%
“…Gautam and Dill-Macky (2012) found similar ndings for F. graminearum isolates on bread wheat cultivars exhibiting various resistance levels. Therefore, it is hypothesized that there must be other factors besides toxins which participate to isolate aggressiveness (Mesterhazy 2020(Mesterhazy , 2024.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have speculated on the negative correlation between FHB severity, plant height, and anther exclusion. It has been suggested that tall genotypes without anthers could have some level of resistance against FHB [ 87 , 88 , 89 , 90 , 91 ]. Recent studies have uncovered the underlying mechanism of glutathione S-transferase (GST) encoded by Fhb7.…”
Section: Important Unresolved Questionsmentioning
confidence: 99%